2017
DOI: 10.3906/sag-1508-42
|View full text |Cite
|
Sign up to set email alerts
|

Social support and quality of life in a group of cancer patients (Ankara, Turkey)*

Abstract: Introduction There were 14.1 million new cancer cases, 8.2 million cancer deaths, and 32.6 million people living with cancer (within 5 years of diagnosis) in 2012 worldwide (1). Cancer represents a tremendous burden on patients, families, and societies (2). Cancer is firmly at the forefront of the Turkish health agenda with a total cancer incidence of 269.7 in males and 173.3 in females per 100,000 world standard population (3,4).Treatment methods, symptom control, and the sustaining of physiological, psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…Our study of Gypsy and Travellers' cancer beliefs and practices support a wider body of literature that highlight the pivotal roles that social relationships play in engaging marginalised populations in health programmes (Roy, 2011;Yilmaz et al, 2017). reporting a higher number of friends and relatives living locallyeven in conventional housing-and with higher than average levels of social activity with non-resident family and friends (Iddenden et al, 2008;Smith, 2008).…”
Section: Experiences Of Cancer Care In Formal Health Settingssupporting
confidence: 68%
“…Our study of Gypsy and Travellers' cancer beliefs and practices support a wider body of literature that highlight the pivotal roles that social relationships play in engaging marginalised populations in health programmes (Roy, 2011;Yilmaz et al, 2017). reporting a higher number of friends and relatives living locallyeven in conventional housing-and with higher than average levels of social activity with non-resident family and friends (Iddenden et al, 2008;Smith, 2008).…”
Section: Experiences Of Cancer Care In Formal Health Settingssupporting
confidence: 68%
“…We also noticed that the monthly income of patients plays an important role in their postoperative quality of life. This finding is consistent with the results reported by earlier studies (Blackburn et al, 2019;Jansen van Rensburg et al, 2017;Yilmaz et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…We also noticed that the monthly income of patients plays an important role in their postoperative quality of life. This finding is consistent with the results reported by earlier studies (Blackburn et al., 2019; Jansen van Rensburg et al., 2017; Yilmaz et al., 2017). Endometrial cancer is a financially draining disease with a long duration, and many patients incur a tremendous economic burden while overcoming this disease.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding income, we found that a higher income was associated with greater perceived social support and RFE, GH. A study from Turkey ( Yilmaz et al, 2017 ) showed that there was a statistically significant association between social support and HRQoL, and that the best predictor that had an effect on perceived social support scores was perceived economic status (both middle, and good to very good economic status). Similar results were reported in a study conducted in the United States with 136 elderly cancer patients, diagnosed with breast, colon, lung, and prostate cancer, where low-income patients had poorer health and social support than higher-income patients ( Schwartz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%